Assessing the challenges of condition assessment of steel-concrete (SC) composite elements using NDE. (June 2022) - Fülöp, Ludovic; Ferreira, Miguel; Tuhti, Antti; Rapaport, Guy
Abstract: Steel-concrete (SC) is a structural typology and construction method in which continuous steel plates are used on the surfaces of concrete walls or slabs, having dual role of formwork and longitudinal reinforcement. The continuous steel-plates on both sides of the concrete element improve economy by prefabrication, but hinder the use of traditional non-destructive evaluation (NDE) to assess the condition of the concrete. In this research, conventional NDE techniques were investigated with regards to their suitability for SC elements, with focus on detection of mechanical damage. Tests were performed on large-scale, mechanically damaged, SC elements. The deployed NDE methods were based on ultrasonic measurements using: the pulse echo technique; radiographic inspection; ultrasound 3D tomographer; impact-echo (IE); impulse-response (IR) and ground penetrating radar (GPR). It was assessed whether cracks of different sizes in the SC beams could be detected through the steel-plated surface. Perpendicular and oblique cracks of 0.1–2.5 mm width were studied. Results: show that ultrasonic testing and GPR were not suitable for testing through the steel surface, due to loss of the transmitted energy in the steel plates. Mechanical impact-based testing systems revealed promising results to detect cracks and de-bonding. Radiographic testing was successful in detecting the presence of cracks in cases when these had sufficient opening and length. Highlights: Ultrasound based NDE and GPR have limitations in SC elements. Impulse-Response (IR) is suitable for evaluating bond of steel to concrete in SC. Impact-Echo (IE) is suitable for detecting internal cracks in the concrete. X-raying detected cracks down to width of 1 mm.